Alpha synuclein post translational modifications: potential targets for Parkinson’s disease therapy? - Brembati, Viviana; Faustini, Gaia; Longhena, Francesca; Bellucci, Arianna (Frontiers in Molecular Neuroscience, 2023)
Parkinson’s disease (PD) is the most common neurodegenerative disorder with motor symptoms. The neuropathological alterations characterizing the brain of patients with PD include the loss of dopaminergic neurons of the nigrostriatal system and the presence of Lewy bodies (LB), intraneuronal inclusions that are mainly composed of alpha-synuclein (α-Syn) fibrils. The accumulation of α-Syn in insoluble aggregates is a main neuropathological feature in PD and in other neurodegenerative diseases, including LB dementia (LBD) and multiple system atrophy (MSA), which are therefore defined as synucleinopathies. Compelling evidence supports that α-Syn post translational modifications (PTMs) such as phosphorylation, nitration, acetylation, O-GlcNAcylation, glycation, SUMOylation, ubiquitination and C-terminal cleavage, play important roles in the modulation α-Syn aggregation, solubility, turnover and membrane binding. In particular, PTMs can impact on α-Syn conformational state, thus supporting that their modulation can in turn affect α-Syn aggregation and its ability to seed further soluble α-Syn fibrillation. This review focuses on the importance of α-Syn PTMs in PD pathophysiology but also aims at highlighting their general relevance as possible biomarkers and, more importantly, as innovative therapeutic targets for synucleinopathies. In addition, we call attention to the multiple challenges that we still need to face to enable the development of novel therapeutic approaches modulating α-Syn PTMs.